Green Technologies for Rural Development. - Al Mamun, Abdullah. (Tufts University. Tisch Library., 2020)
This presentation describes the background, innovations, research, and technologies at the Rural Development Academy in Bangladesh.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy